Matemática financeira contextualizada em sistemas de amortização e impostos de renda - Batista Júnior, Ricardo Inácio [UNESP] (2014)
Financial transactions obey principles based on the most rudimentary knowledge of discrete mathematics. These principles are grounded in knowledge involving discrete variables, such as sequences, progressions, di erence equations , etc. They serve as a basis for understanding the concepts of interest, simple or compound, Amortization System and Income Tax